Complement activation in polycystic ovary syndrome occurs in the postprandial and fasted state and is influenced by obesity and insulin sensitivity - Lewis, Ruth D.; Narayanaswamy, Anil K.; Farewell, Daniel; Rees, Dafydd Aled (Clinical endocrinology (Oxford), 2021)
Objective Polycystic ovary syndrome (PCOS) is associated with metabolic risk. Complement proteins regulate inflammation and lipid clearance but their role in PCOS‐associated metabolic risk is unclear. We sought to establish whether the complement system is activated in PCOS in the fasting and postprandial state. Design Case‐control study. Patients Fasting complement levels were measured in 84 women with PCOS and 95 healthy controls. Complement activation post‐oral fat tolerance test (OFTT) was compared in 40 additional subjects (20 PCOS, 20 controls). Measurements Activation pathway (C3, C4, C3a(desArg), factor B, factor H, properdin, Factor D) and terminal pathway (C5, C5a, terminal complement complex [TCC]) proteins were measured by commercial or in‐house assays. Results Fasting C3, C3a(desArg) and TCC concentrations were increased in insulin‐resistant (adjusted differences: C3 0.13 g/L [95%CI 0‐0.25]; C3a(desArg) 319.2 ng/mL [19.5‐619]; TCC 0.66 μg/mL [0.04‐1.28]) but not in insulin‐sensitive women with PCOS. C3 and factor H levels increased with obesity. Post‐OFTT, C3 and C4 levels increased to a similar extent in PCOS subjects and controls, whist factor H levels increased more in women with PCOS compared to controls (adjusted differences (area under the curve): 12 167 μg min/mL [4942‐19 392]), particularly in the presence of concomitant obesity. Conclusions Activation and terminal complement pathway components are elevated in patients with PCOS, especially in the presence of insulin resistance and obesity.